1999
DOI: 10.1046/j.1523-1755.1999.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in the histopathology of idiopathic nephrotic syndrome in children

Abstract: Our study showed that the incidence of FSGS in children with idiopathic nephrotic syndrome has increased recently. Furthermore, in African American children. FSGS is the most common cause of nephrotic syndrome. These findings may have significant implications in the management of childhood nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
146
5
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 20 publications
17
146
5
11
Order By: Relevance
“…This variation might be related to differences in ethnic composition, biopsy indication policies, or periods of observation analyzed. A trend toward an increasing incidence of FSGS has been noted in several studies (9)(10)(11). The other, much rarer histopathologic entities DMS, membranoproliferative GN, and membranous nephropathy typically presented with milder hypoalbuminemia and a slightly higher prevalence of hypertension than MCN, MesPGN, and FSGS.…”
Section: Discussionmentioning
confidence: 85%
“…This variation might be related to differences in ethnic composition, biopsy indication policies, or periods of observation analyzed. A trend toward an increasing incidence of FSGS has been noted in several studies (9)(10)(11). The other, much rarer histopathologic entities DMS, membranoproliferative GN, and membranous nephropathy typically presented with milder hypoalbuminemia and a slightly higher prevalence of hypertension than MCN, MesPGN, and FSGS.…”
Section: Discussionmentioning
confidence: 85%
“…Early identification and management of these abnormalities, even before the decline of GFR, could ameliorate the growth retardation and renal osteodystrophy that invariably affects children with more advanced chronic kidney disease (CKD) (11). This is particularly relevant to patients with NS because a growing incidence of corticosteroid-resistant NS secondary to focal segmental glomerulosclerosis (12,13) is a leading cause of CKD stages 4 to 5 in children (14).…”
mentioning
confidence: 99%
“…This observation can be attributed to the fact that we had performed biopsies in a selected group of patients who responded poorly to steroid treatment. Also this observation may be related to the increasing frequency of FSGS as indicated in the study of Bonilla-Felix et al 20 In previous studies, the incidence of hematuria has been reported to be higher in patients with steroid resistance. 21,22 Banaszak and Banaszak 23 detected that the frequency of microscopic hematuria significantly increased with the increased rate of steroid resistance frequency.…”
mentioning
confidence: 81%